Clinic Satisfaction Tool Improves Communication and Provides Real-Time Feedback. Issue 4 (14th April 2018) - Zakare-Fagbamila, Rasheedat T; Howell, Elizabeth; Choi, Ashley Y; Cheng, Tracy Z; Clement, Mary; Neely, Megan; Gottfried, Oren N
Abstract: BACKGROUND: Patient-reported assessments of the clinic experience are increasingly important for improving the delivery of care. The Clinician and Group Consumer Assessment of Healthcare Providers and Systems (CG-CAHPS) survey is the current standard for evaluating patients' clinic experience, but its format gives 2-mo delayed feedback on a small proportion of patients in clinic. Furthermore, it fails to give specific actionable results on individual encounters. OBJECTIVE: To develop and assess the impact of a single-page Clinic Satisfaction Tool (CST) to demonstrate real-time feedback, individualized responses, interpretable and actionable feedback, improved patient satisfaction and communication scores, increased physician buy-in, and overall feasibility. METHODS: We assessed CST use for 12 mo and compared patient-reported outcomes to the year prior. We assessed all clinic encounters for patient satisfaction, all physicians for CG-CAHPS global rating, and physician communication scores, and evaluated the physician experience 1 yr after implementation. RESULTS: During implementation, 14 690 patients were seen by 12 physicians, with a 96% overall CST utilization rate. Physicians considered the CST superior to CG-CAHPS in providing immediate feedback. CG-CAHPS global scores trended toward improvement and were predicted by CST satisfaction scores ( P  < .05). CG-CAHPS physician communication scores were also predicted by CST satisfaction scores ( P  < .01). High CST satisfaction scores were predicted by high utilization ( P  < .05). Negative feedback dropped significantly over the course of the study ( P  < .05). CONCLUSION: The CST is a low-cost, high-yield improvement to the current method of capturing the clinic experience, improves communication and satisfaction between physicians and patients, and provides real-time feedback to physicians.